2011
DOI: 10.3109/0167482x.2011.626940
|View full text |Cite
|
Sign up to set email alerts
|

Prior psychiatric inpatient care and risk of cesarean sections: a registry study

Abstract: This study of 17,443 childbearing women, investigated the relationship between hospital admissions 5 years prior to index birth, type of mental disorders and risk factors for mode of delivery. Hospital based electronic perinatal medical records between 2001 and 2006, were linked with the Swedish National Inpatient Care Registry 1996-2006. Of all the women, 39.3% had had inpatient care prior to index birth (27.3% had had obstetric, 10.1% somatic, and 1.9% psychiatric inpatient care). Diagnoses of mental disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Some “nonmedically” indicated cesareans might be performed on a psychiatric indication when a concomitant severe fear of childbirth and mental illness is present. Mental illness has been associated with an increased risk of emergency cesarean . In the present study, a higher EDS score among primiparous women was associated with emergency cesarean, adjusted OR 1.62 (95% CI 1.12–2.36).…”
Section: Discussionsupporting
confidence: 44%
“…Some “nonmedically” indicated cesareans might be performed on a psychiatric indication when a concomitant severe fear of childbirth and mental illness is present. Mental illness has been associated with an increased risk of emergency cesarean . In the present study, a higher EDS score among primiparous women was associated with emergency cesarean, adjusted OR 1.62 (95% CI 1.12–2.36).…”
Section: Discussionsupporting
confidence: 44%
“…Also, a single item descriptor was used to measure maternal mental health problems as a screening tool but validated screening instruments were not used and it is unclear whether women who reported mental health problems received a formal diagnosis, further investigation, or any treatment. These limitations apply to other similar studies [20,21,33] and these issues would need to be addressed in a properly-constructed prospective study.…”
Section: Cs % Non-cs % or (95% Ci) P Pregnancy Factorsmentioning
confidence: 96%
“…One study linked data from the Swedish National Inpatient Care Registry 1996-2006 with hospital perinatal records for over 17,000 women, and found that hospital admissions in the five years prior to index birth were associated with an increased risk of elective CS (adjusted OR 2.16, 95% CI 1.34, 4.42), and emergency CS (adjusted OR 1.60, 95% CI 1.09, 2.37), as well as with markers of mental ill-health in pregnancy identified in perinatal records [21]. Another study examined 6,000 nulliparous women and found that report of stress (adjusted OR 1.66, 95% CI 1.34, 2.06), sleep difficulties (adjusted OR 1.57, 95% CI 1.14, 2.16), and worry (adjusted OR 1.41, 95% CI 1.10, 1.79) were all associated with an increased rate of emergency CS in first-time mothers [20].…”
Section: Cs % Non-cs % or (95% Ci) P Pregnancy Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study by Wangel et al . found an increased risk of emergency and elective caesarean section for women with a history of psychiatric inpatient care and self‐reported mental ill health during their pregnancy. In previous published research, we reported higher rates of assisted vaginal delivery and emergency caesarean rates in women with SMI attending a specialist antenatal clinic, the Childbirth and Mental Illness Clinic (CAMI clinic) at King Edward Memorial Hospital (KEMH) in Perth, Western Australia (WA).…”
Section: Introductionmentioning
confidence: 98%